Blasu - Ros, Manon Steffan (Y Lolfa, 2020)
Whilst looking back on her life and the family and friends who accompanied her along the way, memories resurface for Pegi. But not every memory is sweet, and some secrets leave a bitter taste. Intro – Diolchiadau – Hawlfraint – Pegi – Mai Davies – Sion Pugh – Gwynfor Daniels – Davey Hoyle – Jennie Williams – Francis Phyllip – Annie Vaughan – Issac Phyllip – Kenneth Davies – Elen Pugh – Dr Thomas – Menna Arthur – Francis Phyllip – Merfyn Thomas – Susan Vaughan – Huw Phyllip – Annie Vaughan – Sion Phyllip – Jac Vaughan – Huw Phyllip – Pegi – Jonathan Phyllip – Y Lolfa.
Description based on publisher supplied metadata and other sources
Keywords: Electronic books